ANALISIS KETERAMPILAN MENULIS HURUF TEGAK BERSAMBUNG MELALUI PENGGUNAAN BUKU TULIS HALUS KELAS IIA SDN KEBONSAWAHAN 02 JUWANA - Anita Tri Yuniarti Husnul Had, dan Mudzanatun (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2020)
AbstractWriting upright letters is one form of writing skills with regard to rules and aesthetic values that combine letters that are connected with each other in a rounded shape. The skill of writing upright letters on class II A students at SDN Kebonsawahan 02 Juwana is quite good, but most students write with no regard for accuracy. There are still students who experience confusion when writing upright letters, the use of soft writing aids is used by students to make writing letters and writing easier. This study aims to describe writing letters upright through the use of fine line books in class IIA SDN Kebonsawahan 02. This type of research is qualitative descriptive. Data collection in this study was conducted by methods (1) observation, (2) interviews, and (3) questionnaires. The results of the study showed that all students of class IIA SDN Kebonsawahan 02 Juwana were able to write upright letters. The use of fine line books is very useful to facilitate and facilitate students when writing upright letters so that the writing looks neat and beautiful. The number of correct procedure formulations when writing connecting letters in fine notebooks, resulting in not all students knowing thoroughly about these procedures. This creates confusion when writing for some students so that many errors arise in writing connect letters in fine line books. Of the 21 students of class IIA SDN Kebonsawahan 02 Juwana, only one student was found whose results did not experience any errors at all. All other students can only write upright letters in a fine line book without including the correct steps in writing.Keyword: Writting skills, upright letters,fine line books